PENGARUH EARNING PER SHARE, BOOK VALUE PER SHARE, RETURN ON EQUITY DAN ASSET TURNOVER RATIO TERHADAP HARGA SAHAM (Studi Pada Perusahaan Emiten Sektor Perbankan Di Bursa Efek Indonesia) - Putri Endah Kurnia, 12.05.52.0134; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of Earning Per Share (EPS), Book Value per Share Return On Equity and Asset Turnover Ratio Stock Price at the aforementioned Company Banking sector in Indonesia Stock Exchange The population used in this study were banking companies go public and issue audited financial statements and published on the Indonesia Stock Exchange (BEI), which was taken during the 4 year period, namely from 2012 to 2015. The sampling technique used purposive sampling. The criteria for the sample in this study is the company to publish financial statements and presents complete information needed in this study for 4 years in a row; Companies that have a positive net income; had complete data for the study variables. The sample in this study were 26 banking. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: Earning per share (EPS) significant positive effect on stock prices. BVS no significant positive effect on stock prices. Return On Equity (ROE) significant positive effect on stock prices. ATR is significant positive effect on stock prices.Keywords:Â Earning Per Share, Book Value Per Share, Return On Equity, Asset Turnover Ratio and Stock Price